Seizure and cognitive outcomes of epilepsy surgery in infancy and early childhood - Ramantani, Georgia; Kadish, Navah; Strobl, Karl; Brandt, Armin; Stathi, Angeliki; Mayer, Hans; Schubert-Bast, Susanne; Wiegand, Gert; Korinthenberg, Rudolf; Stephani, Ulrich; van Velthoven, Vera; Zentner, Josef; et al. (European journal of paediatric neurology, 2013)
Aims - To investigate seizure and developmental outcomes following epilepsy surgery in very young children and determine their predictive factors. - Methods - We retrospectively reviewed the clinical data, surgical variables, and outcomes of 30 children under 3 years of age that underwent resection for refractory focal epilepsy in our institution in 2001-2011. - Results - Seizure onset was in the first year of life in 27 (90%) cases and mean age at surgery was 20 months (range 5-33.6). Pathology consisted of cortical malformations in 24 (80%) cases, glioneuronal tumour and infarction with or without cortical dysplasia in three (10%) cases each. Morbidity was comparable with older paediatric cohorts. At 1-11.6 year follow-up (mean 4.1) 21 of 30 (70%) children achieved seizure freedom (Engel I), six (20%) demonstrated worthwhile improvement (Engel II/III) and three (10%) did not benefit from surgery (Engel IV). Intralobar lesionectomy more often resulted in seizure freedom than multilobar or hemispheric surgery. The abundance of non-regional interictal and ictal EEG findings did not preclude seizure freedom. Presurgical developmental impairment was established in 25 of 28 (89%) children; its severity correlated with longer epilepsy duration and determined postoperative developmental outcome. Developmental progress was established in 26 out of 28 (93%) children following surgery, showing stabilized trajectories rather than catch-up. - Conclusions - Resective surgery in very young children is safe and effective in terms of seizure control and developmental progress. Our findings underline the importance of early intervention in order to timely stop seizures and their deleterious effects on the developing brain.
Gesehen am 14.12.2021